Stades method for surgical correction of upper eyelid trichiasis-entropion: results and follow-up in 21 cases - Laus, José Luiz [UNESP]; Vicenti, Felipe António Mendes [UNESP]; Bolzan, Aline Adriana [UNESP]; Galera, Paula Diniz [UNESP]; Sanches, Rodrigo Cezar [UNESP] (Universidade Federal de Santa Maria, 2000)
Trichiasis is a condition in which lhe cuia and facial hairs grow toward lhe córnea or the conjunctiva. The hairs arising from normal sites are pointed aí an abnormal direction. This condition may be caused by prominent nasal folds, entropion, blepharospasm, slipped facial mask and dermoids. The upper eyelid trichiasis-entropion with lower eyelid entropionectropion frequentiy occurs in oíder English Cocker Spaniels. The ocular signs often are epiphora, blepharospasm, conjunctivitis, keratitis and comeal ulceratíon. Treatment depenas on the severity ofthe condition and must eliminate the ocular contact by misdirected cuia that irritate the eyeball. This report presents a retrospective study of21 patients with bilateral diffüse trichiasis (15 English Cocker Spaniels; 2 Basset hounds; l Bloodhound; l Fila Brasileiro and 2 mongrel dogs). The procedure described by Stades was employed m ali cases. Postoperatively, topical chioramphenicol oiníment (qid) was appiied in the conjunctival soe and on the open woundfor 2 weeks. Sutures were removed 10 days after surgery. Correction ofpositioning ofthe upper eyelid was successfúl and its apposition to córnea was normal. In most of the cases the reepithelialiwtion was complete one month after surgery. No signs ofrecurrence werefound and there appeared to be no loss of normal fünction of the eyelid in the 21 dogs available for follow-up examination in a maximum period of 36 months.

Triquíase é a condição na qual os cílios e os cabelos faciais crescem em direção à córnea ou conjuntiva. Os pêlos que surgem de locais normais estão apontados em uma direção anormal. Essa condição pode ser causada por dobras nasais proeminentes, entrópio, blefarospasmo, pele facial redundante e dennóides. A triquíase-entrópio da pálpebra superior associada ao entrópio-ectrópio da pálpebra inferior, frequentemente, ocorre em English Cocker Spaniels idosos. Os sinais oculares são frequentemente epífora, blefarospasmo, conjuntivite, ceratite e ulceração comeana. O tratamento depende da severidade da condição e deve eliminar o contato dos cílios com o globo ocular. Este trabalho apresenta um estudo retrospectivo de 21 pacientes com triquíase difusa bilateral (15 English Cocker Spaniels; 2 Basset hounds; l Bloodhound; l Fila Brasileiro e 2 coes sem raça definida). Empregou-se o procedimento descrito por Stades em todos os casos. No pós-operatório, aplicou-se pomada à base de cloranfenicol (qid) no saco conjuntival e na ferida aberta durante duas semanas. Removeram-se as suturas 10 dias após a cirurgia. Obteve-se êxito na correção do posicionamento da pálpebra superior e observou-se sua justaposição normal em relação à córnea. Ocorreu reepiteliwção completa da ferida um mês após a cirurgia. Não houve sinais de recidiva ou perda da função da pálpebra nos 21 cães avaliados por 36 meses.
Método de Stades para a correção da triquíase-entrópio da pálpebra superior: resultados e acompanhamento de 21 casos
Keywords: trichiasis; entropion; surgery; Stades; triquíase; entrópio; cirurgia; Stades